Effects of Epoxidised Natural Rubber on the Oil Resistance Property of NBR/ENR Blends used for Safety Footwear Application - Mohd Hanif, H.; C. Yong, K. (International Journal of Engineering and Technology, 2019)
Epoxidised natural rubber, ENR has emerged as a sustainable material for many applications due to its unique properties. This study sets out to investigate the effects of ENR on the oil resistance property of nitrile rubber, NBR composites used for safety footwear application. Blends of NBR/ENR i.e. 100/0, 90/10, 80/20, 70/30, 60/40 and 50/50 were prepared and tested for their oil resistance property and other physical properties such as hardness, tensile properties and abrasion loss. Results showed that varying the amount of ENR did not significantly affect the hardness and tensile properties of the composites. Nonetheless, it was found that ENR content highly influences the abrasion loss of the composites in which the abrasion resistance decreased with further addition of ENR contents. Despite the increase in oil swelling of the composites with increasing ENR content, the oil swelling values are considered low (< 5% volume change), indicating superior oil resistance property of the composites. These results confirm the possibility of ENR as a sustainable material for the production of eco-friendly composites with high oil resistance property for the footwear industry.Â Â